Demographic Characteristics of Mothers Related to Mother's Knowledge in Providing MP-ASI - Putu Sukma Megaputri; Gusti Ayu Komang Sutiastari (Program Studi Keperawatan Universitas Muhammadiyah Tasikmalaya, 2023)
Complementary food for brastfeeding (CFB) can ideally be given at the age of 6 months. But in fact there are still mothers who give CFB when the baby is not yet 6 months old. This causes an increase in mortality and morbidity in infants. The purpose of this study was to analyze the characteristics associated with complementary feeding. This research method is quantitative with a cross sectional approach. The sampling technique in this study was purposive sampling with a total sample of 54 respondents. The results of the study reported that the higher the mother's education, the better the knowledge about giving CFB automatically (OR 7.2, p value 0.005). Mothers with primigravidas increased the risk of good knowledge in giving complementary foods (OR 4.3, nilap p 0.04). The conclusion is that the characteristics associated with increasing knowledge of complementary feeding are high maternal education and parity.